Biological activities of essential oil extracted from leaves of Atalantia sessiflora Guillauminin Vietnam - Le, Nhan Trong; Donadu, Matthew Gavino; Ho, Duc Viet; Doan, Tuan Quoc; Le, Anh Tuan; Raal, Ain; Usai, Donatella; Sanna, Giuseppina; Marchetti, Mauro; Usai, Marianna; Diaz, Nicia; Rapelli, Paola; et al. (The Journal of Infection in Developing Countries, 2020)
Introduction: The present study aimed to determine the chemical compositions and bioactivities of the essential oil of Atalantia sessiflora Guillaumin (A. sessiflora), including antibacterial, antimycotic, antitrichomonas, anti-inflammatory and antiviral effects. Methodology: The essential oil from leaves of A. sessiflora was extracted by hydrodistillation using a Clevenger apparatus. Chemical compositions of oil were identified by GC/MS. Antimicrobial and antitrichomonas activity were determined by the microdilution method; anti-inflammatory and antiviral were determined by the MTT method. Results: The average yield of oil was 0.46 ± 0.01% (v/w, dry leaves). A number of 45 constituents were identified by GC/MS. The essential oil comprised four main components. The oil showed antimicrobial activities against Gram-positive strains as Staphylococcus; Gram-negative bacteria such as Klebsiella pneumoniae and Escherichia coli; and finally four Candida species. Enterococcus faecalis and Pseudomonas aeruginosa were least susceptible to the oil of A. sessiflora, as seen in their MIC and MLC values over 16% (v/v). Activity against Trichomonas vaginalis was also undertaken, showing IC50, IC90 and MLC values of 0.016, 0.03 and 0.06% (v/v) respectively, after 48 hours of incubation. The oil of A. sessiflora displayed activity against the nitric oxide generation with the IC50 of 95.94 ± 6.18 µg/mL. The oil was completely ineffective against tested viruses, ssRNA+, ssRNA-, dsRNA, and dsDNA viruses. Conclusions: This is the first yet comprehensive scientific report about the chemical compositions and pharmacological properties of the essential oil of A. sessiflora. Further studies should be done to evaluate the safety and toxicity of A. sessiflora oil.